Metabolic syndrome in patients with hematological diseases. Issue 4 (August 2012) - Annaloro, Claudio; Airaghi, Lorena; Saporiti, Giorgia; Onida, Francesco; Cortelezzi, Agostino; Deliliers, Giorgio Lambertenghi
The term metabolic syndrome (MS) defines a clustering of cardiovascular risk factors, formerly known as syndrome X. There is some debate about the diagnostic criteria; but the most widely accepted framework is that defined by the National Cholesterol Education Program Adult Treatment Panel III, which requires the simultaneous occurrence of at least three of abdominal obesity, arterial hypertension, hyperglycemia, hypertrigliceridemia and low high-density lipoprotein cholesterol (HDL-C). The prevalence of MS increases with age and varies depending on genetic factors. An abnormally high prevalence has been observed in patients with heterogeneous conditions, such as solid organ transplant recipients, AIDS patients and long-term cancer survivors. As some of the pathogenetic factors possibly involved include cyclosporine A, corticosteroids and cancer chemoradiotherapy, it is possible that MS may also be a complication in hematological patients. Some of the characteristics of MS have been reported with a certain frequency in thalassemia patients, and are mainly attributed to iron overload. Impaired hemostasis is a feature of MS rather than a factor predisposing to its development. In oncohematology, an abnormally high prevalence of MS features has been observed in survivors of pediatric acute lymphoblastic leukemia. In addition to corticosteroid- and cancer therapy-related hypogonadism, hypothyroidism and defective growth hormone incretion are other factors related to the development of MS. Moreover, the highest frequency of MS is observed in hematopoietic stem cell transplantation (HSCT) recipients. Pediatric patients and allogeneic HSCT recipients have been the subject of foremost investigations; but adult patients and autologous HSCT recipients have also been studied more recently. A wide range of factors may contribute to the development of MS in HSCT recipients. Unfortunately, the real entity of the problem is far from clear because of the retrospective design of the studies, the limited size of their populations and their heterogeneous selection criteria, thus making it difficult to determine whether MS is a transient and possibly reversible phenomenon or a true late effect of the procedure.